Mengembangkan Kecerdasan Emosional Anak melalui Kebiasaan Bercerita (Dongeng) - Anwar Efendi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Folklore is a part of medium to enhancing children’s intelligence. Motivation to perform well (need for achievement) is mentality aspect that most necessary for society which been developing. That mentality aspect could be inspired from society’s own folklore. Therefore its vital to accustom the tell a story activity, either in school and family. Story socialization is early stage from reading habit, inner experience, and investing values as child’s behavioral reference standards in life. Tell a story activity also the part of child stimulation in the form of verbal, nonverbal, intellectual, and tactile. Story can have a positive impact to child’s socio-emotional aspect. Through tell a story activity, parent and teacher can train child’s emotion in order to improving emotional intelligence.